Nafion lonomer-based single component electrolytes for aqueous Zn/MnO2 batteries with long cycle life - Ghosh, Meena; Vijayakumar, Vidyanand; Anothumakkool, Bihag; Kurungot, Sreekumar (ACS Sustainable Chemistry & Engineering, 2020)
Recently, aqueous rechargeable Zn/MnO2 batteries are emerging as promising energy storage aids owing to their improved safety, low cost of fabrication, and high energy density. However, the rapid decay of capacity during extended charge- discharge cycles hinders the prospect of this technology beyond lab-scale. In the conventional Zn/MnO2 cell, additives such as Mn2+ have been used to tackle the stability issue. Here, we demonstrate that cycling performance of the Zn/MnO2 cell can be improved substantially by using Nafion ionomer as the separator in combination with zinc-ion conducting electrolytes. The Nafion ionomer-based Zn/MnO2 cells do not require any Mn' additive in the electrolyte and hence termed as ``single component'' electrolytes. The postmortem study of the post-cycled electrodes reveals that the structural evolution of both the anode and cathode in various electrolytes (1 M Zn(CF3SO3)(2), 1 M ZnSO4 center dot 7H(2)O, and 3 M ZnSO4 center dot 7H(2)O) during prolonged cycling significantly influences the cycle life of the respective cells. Optimizing the Nafion ionomer membrane with a suitable electrolyte could render the desired combination of high capacity and high cycle life for a Zn/MnO2 cell.
Keywords: aqueous Zn-ion batteries; Cycling stability; dendrite suppression; Electrodeposition; MnO2; Nafion ionomer separator; single component electrolyte